2019
DOI: 10.1016/j.parkreldis.2018.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Everyday functioning in Parkinson's disease: Evidence from the Revised-Observed Tasks of Daily Living (OTDL-R)

Abstract: PD patients were slower to complete the OTDL-R, but only less accurate on the telephone use subtest. Poor performance on the telephone use subtest may be related to motor severity, while poor performance on the financial management subtest was related to attention and working memory. Overall, the findings warrant future investigation to determine the validity and reliability of the OTDL-R in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
2
10
2
Order By: Relevance
“… “We reported significant early improvements (3 months) in the HRQoL and ADLs, and these benefits increased over time (6 months); however, further improvement between 6 and 12 months was nonsignificant. (Francesca V. Lopez et al, 2018) 75 “Clinical severity of PD was assessed using the H&Y stage, UPDRS, and Schwab and England functional disability scores” “Aims of the current study were to examine and determine the impact of cognitive, motor, and mood symptoms on Observed Tasks of Daily Living (OTDL-R) performance in PD.” 19 patients Mean age −63.5 “Patients with PD were significantly slower to complete the OTDL-R and performed worse on only the telephone use subtest, relative to the HC group.” (Antonio Nicolas Puente, 2016) 71 “Comprehensive neuropsychological evaluation, The Lawton IADLs and Physical Self-Maintenance Scales-rater form, Executive functioning questionnaire.” “Authors put forward the hypothesis that informant rated executive functioning (EF) may prove useful in providing incremental validity when forecasting IADLs that go above and beyond EF scores.” 120. Mean age in years 65.1 EF would add incremental validity beyond tests in explaining the performance of IADLs in patients with PD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… “We reported significant early improvements (3 months) in the HRQoL and ADLs, and these benefits increased over time (6 months); however, further improvement between 6 and 12 months was nonsignificant. (Francesca V. Lopez et al, 2018) 75 “Clinical severity of PD was assessed using the H&Y stage, UPDRS, and Schwab and England functional disability scores” “Aims of the current study were to examine and determine the impact of cognitive, motor, and mood symptoms on Observed Tasks of Daily Living (OTDL-R) performance in PD.” 19 patients Mean age −63.5 “Patients with PD were significantly slower to complete the OTDL-R and performed worse on only the telephone use subtest, relative to the HC group.” (Antonio Nicolas Puente, 2016) 71 “Comprehensive neuropsychological evaluation, The Lawton IADLs and Physical Self-Maintenance Scales-rater form, Executive functioning questionnaire.” “Authors put forward the hypothesis that informant rated executive functioning (EF) may prove useful in providing incremental validity when forecasting IADLs that go above and beyond EF scores.” 120. Mean age in years 65.1 EF would add incremental validity beyond tests in explaining the performance of IADLs in patients with PD.…”
Section: Resultsmentioning
confidence: 99%
“… 22 , 56 66 These articles focused on ADLs, iADLs, and QoL. 61 , 64 , 67 75 In addition, five studies focused on one country. 59 , 61 , 62 , 65 , 67 The subject sample size varied greatly across articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated objective IADL performance limitations in people with PD without dementia. 28 , 29 , 30 , 31 , 32 However, the evidence is inconsistent regarding the underlying cognitive deficits that contribute to these limitations. Whereas some studies have found associations between IADL performance and global cognitive impairment 27 , 28 or deficits in specific cognitive domains such as cognitive flexibility, attention, memory, and executive functioning, 29 , 32 , 33 , 34 , 35 , 36 others have found no relationships.…”
mentioning
confidence: 99%
“… 28 , 29 , 30 , 31 , 32 However, the evidence is inconsistent regarding the underlying cognitive deficits that contribute to these limitations. Whereas some studies have found associations between IADL performance and global cognitive impairment 27 , 28 or deficits in specific cognitive domains such as cognitive flexibility, attention, memory, and executive functioning, 29 , 32 , 33 , 34 , 35 , 36 others have found no relationships. 30 , 31 A better understanding of the cognitive mechanisms of IADL performance limitations in PD may improve detection of and intervention for early functional decline in this population.…”
mentioning
confidence: 99%